Cultivating vegetables free from weeds - Kaur, Ramanjit; Kaur, Simerjeet; Kumar, Dinesh; Bhullar, M S; Kaur, Tarundeep (Indian Horticulture, 2019)
Weed management is one of the most important determinants of successful production of vegetable crops. Weeds reduce crop yields, lower produce quality and increase cost of production. They host pests and diseases thereby raising the need to control them as well. Weeds can be controlled by non-chemical and or chemical methods, but decision regarding method to be used depends on environmental conditions, available labour, weed population, weed type, crop, desired management practices and cost of controlling weeds. The major aim is to keep the weed population below the economic threshold level. An optimal integration of different control methods, therefore needs to be attempted in future research. Furthermore, specific researches on weed management in horticultural crops in India need to be addressed. However, currently available weed management practices including chemical and non-chemical means of weed control in vegetable crops have been presented.